Appalachian social entrepreneurship ecosystem: A framework for rural development. (4th May 2023) - Ricket, Allison L.; Knutsen, Faith Beale; Jolley, G. Jason; Davis, Sarah C.
ABSTRACT: This paper contributes to the gap in the understudied, but increasingly salient, topic of the development of social enterprise ecosystems (SEEs) in rural areas using the Appalachian Ohio SEE as a framework for understanding the development of rural SEEs. Building on prior studies of the successful rural entrepreneurial ecosystem (EE) in Appalachian Ohio, this paper relates the relationship between the EE and SEE in Appalachian Ohio to the context of traditional economic and community development. The case studies reviewed here illustrate the importance of the social capital of regional champions, university as convener and place for ecosystem overlap, and multiple capitals approach to community regeneration. The commonalities identified among cases suggest that a fourth wave of economic development will depend on a healthy intersection of community and economic development that recognizes the need for maintaining real ecosystem services. The SEE framework is especially suited to catalyze this intersection.